2021
DOI: 10.3390/molecules26092424
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of Nrf2 Signaling Pathway in Wound Healing Process

Abstract: Wound healing involves a series of cellular events in damaged cells and tissues initiated with hemostasis and finally culminating with the formation of a fibrin clot. However, delay in the normal wound healing process during pathological conditions due to reactive oxygen species, inflammation and immune suppression at the wound site represents a medical challenge. So far, many therapeutic strategies have been developed to improve cellular homeostasis and chronic wounds in order to accelerate wound repair. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 122 publications
(116 reference statements)
0
23
0
Order By: Relevance
“…Nrf2 negatively regulated the NF-κB signaling pathway and proinflammatory cytokine production by inhibiting oxidative stress-induced NF-κB and preventing the IκB-α (NF-κB inhibitor) proteasomal degradation ( Ma, 2013 ; Saha et al, 2020 ). In addition, several proinflammatory cytokines (e.g., IL-6, TNF-α and IL-1β), growth factors (e.g., epidermal growth factor (EGF), fibroblast growth factor, keratinocyte growth factor (KGF) and vascular endothelial growth factor (VEGF) and MMPs (e.g., MMP-2 and MMP-9) play a role in wound repair consisting of a series of multiple stages including inflammation, proliferation and remodeling ( Shao et al, 2019 ; Suntar et al, 2021 ). Activation of Nrf2 in response to ROS production in inflamed tissues is thus suggested to play a role in promoting wound healing and regulating repair-related inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 negatively regulated the NF-κB signaling pathway and proinflammatory cytokine production by inhibiting oxidative stress-induced NF-κB and preventing the IκB-α (NF-κB inhibitor) proteasomal degradation ( Ma, 2013 ; Saha et al, 2020 ). In addition, several proinflammatory cytokines (e.g., IL-6, TNF-α and IL-1β), growth factors (e.g., epidermal growth factor (EGF), fibroblast growth factor, keratinocyte growth factor (KGF) and vascular endothelial growth factor (VEGF) and MMPs (e.g., MMP-2 and MMP-9) play a role in wound repair consisting of a series of multiple stages including inflammation, proliferation and remodeling ( Shao et al, 2019 ; Suntar et al, 2021 ). Activation of Nrf2 in response to ROS production in inflamed tissues is thus suggested to play a role in promoting wound healing and regulating repair-related inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, proper regulation of oxidative stress in wound microenvironment may play a positive role in promoting wound healing. Recent researches reported that Nrf-2 plays a vital role in alleviating oxidative stress and promoting wound healing [ 11 , 12 ]. The Nrf-2 signal pathway participates in the regulation of antioxidative gene expression and thus improves the cell protection [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the GSH/GSSG ratio can attenuate the oxidative damage of ROS on osteoblasts via the PI3K/Akt-Nrf2 signaling pathways ( Casati et al, 2020 ). Nrf2 is a nuclear factor that regulates gene encoding proteins involved in the response to injury and inflammation, including the production of free radicals ( Süntar et al, 2021 ). When the PI3K/AKT pathway located on the cell membrane is activated, the signal is transmitted to the cytoplasm to release Nrf2 anchored by Kelch-like ECH-associated protein 1 (Keap1) ( Chen et al, 2021a ).…”
Section: Antioxidant Substancesmentioning
confidence: 99%